Spatiotemporal Variations of Focal Mechanism Solutions and Stress Field of the 2019 Changning Ms 6.0 Earthquake Sequence - Zhang, Zhiwei; Liang, Chuntao; Long, Feng; Zhao, Min; Wang, Di (Frontiers in Earth Science, 2022)
The June 17, 2019, MS 6.0 Changning earthquake is the largest recorded event in the Sichuan basin, spatiotemporal variations of stress field may shed light on the seismogenic mechanism of the earthquake. We determined the focal mechanism solutions (FMSs) of 124 earthquakes with MS ≥ 3.0 occurring in the Changning area from April 1, 2007, to February 29, 2020, and analyzed changes of FMSs and stress field before and after Changning earthquake. The Changning aftershocks were predominantly thrust fault earthquakes, followed by strike slip. The P-axis azimuths of the aftershock FMSs were oriented predominantly in the NEE direction, notably differing from the NWW-oriented P-axis azimuths of pre-earthquake FMSs; it shows the rotation of local stress field before and after the Changning earthquake, it is speculated that the change of stress field in Changning area may be caused by long-term water injection and salt mining activities. From the southeast to the northwest of the aftershock zone, the azimuths of principal compressive stress (S1) change from NEE to near-EW in both horizontal and vertical planes. Significant changes occurred in the FMS types and stress field of the aftershock zone following the Changning earthquake, the FMSs became diverse, the S1 azimuth of the Changning area changed from NWW to NEE, and then EW, the plunge and stress tensor variances increased, it reflects that the stress field of the Changning area adjusts continually with time.